2019
DOI: 10.1111/1756-185x.13688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin nanomicelle on the clinical symptoms of patients with rheumatoid arthritis: A randomized, double‐blind, controlled trial

Abstract: Aim Rheumatoid arthritis (RA) is a systemic inflammatory disease. In recent years, new drugs with novel targets have been developed to increase the efficacy of drugs in the treatment of RA. Curcumin has shown potent anti‐inflammatory effects and is considered an anti‐tumor necrosis factor. The present study was conducted to determine the effect of curcumin nanomicelle on the clinical symptoms of patients with RA. Methods This randomized, double‐blind, controlled trial selected 65 eligible RA patients and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 29 publications
2
44
2
Order By: Relevance
“…This, therefore, means that both ginger extract and curcumin may offer an alternative to NSAIDS for patients with knee osteoarthritis who are experiencing negative side effects from standard treatments (Hewlings & Kalman, 2017). The use of nanocurcumin by patients with rheumatoid arthritis was, however, not as promising as no significant differences were observed between the nanocurcumin and control groups (Javadi, Haghighian, Goodarzy, Abbasi, & Nassiri‐Asl, 2019).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This, therefore, means that both ginger extract and curcumin may offer an alternative to NSAIDS for patients with knee osteoarthritis who are experiencing negative side effects from standard treatments (Hewlings & Kalman, 2017). The use of nanocurcumin by patients with rheumatoid arthritis was, however, not as promising as no significant differences were observed between the nanocurcumin and control groups (Javadi, Haghighian, Goodarzy, Abbasi, & Nassiri‐Asl, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Adverse events reported after the use of nanopolyphenols in the included studies were minimal. Of the 18 studies that provided this information, a total of 12 studies reported no adverse effects during or after treatment (Abdolahi et al., 2018; Afshar et al., 2020; Alizadeh et al., 2018; Amorndoljai et al., 2017; Delavarian et al., 2019; Dolati, Aghebati‐Maleki et al., 2018; Farhadi et al., 2018; Gallelli et al., 2020; Hashemzadeh et al., 2020; Javadi et al., 2019; Parohan et al., 2019; Sasaki et al., 2011). Mild adverse events reported include stomachache (Asadi et al., 2019; Asadi, Gholami, Siassi, Qorbani et al., 2019) and nausea (Jazayeri‐Tehrani et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A larger trial with 300 patients with mild-to-moderate UC did not find a significant clinical benefit when using much lower doses of curcumin (450 mg/day) [ 84 ]. Larger, randomized controlled trials in RA using moderate doses of curcumin (from 120 mg to 1.2 g a day) demonstrated an improvement in clinical disease activity scores, tender joint count, and swollen joint count [ 52 , 85 , 86 ]. Though clinical trials of curcumin use in psoriatic disease are limited, in vitro studies suggest a potential benefit [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nanomicelles enable prolonged circulation, reduced administered dose, and diminished toxicity of therapeutics. Such advantages of nanomicelles have been proved by a clinical trial in which RA patients orally undertaking the curcumin nanomicelles exhibited positive changes in joint scores, tender joint count, and swollen joint count [24].…”
Section: Trans-resveratrol Cis-resveratrolmentioning
confidence: 99%